Simultaneous quantification of apolipoproteins A-I, E, and J in human plasma by LC-MS/MS for clinical application to diabetes mellitus complicated with cardiovascular disease. Issue 26 (6th June 2022) - Li, Pengfei; Cong, Yuting; Zhang, Wen; Wang, Lefeng; Ren, Lulu; Li, Xin; Yang, Song; Zhang, Zhiyong; Li, Guoqing; Liu, Lihong
Abstract : Simultaneous quantification of apolipoproteins A-I, E, and J in human plasma by LC-MS/MS. Abstract : Apolipoproteins (Apos) play an important role in regulating plasma lipid concentration. Complex disorders of Apos are highly related with diabetes mellitus, cardiovascular and other diseases. Direct measures of lipoprotein fractions for risk assessment suffer from inaccuracy in the dyslipidemia and pathological states. Therefore, a reliable precise assay will be of high clinical utility. LC-MS/MS methods with multiple reaction monitoring modes have proven suitable for multiplexed quantification. We aimed to develop a simple, cost-effective and amenable LC-MS/MS assay for quantification of ApoA-I, ApoE and ApoJ in human plasma. Standards were constructed from substitute matrix and proteotypic peptides for external calibration and corresponding stable isotope labeled peptides were added as internal standards to remove matrix effects. Analytical validation of the assay included the assessment of linearity, accuracy (RE: −3.02% to 5.32%), intra-assay precision (RSD: 2.50% to 6.56%), inter-assay precision (RSD: 0.78% to 6.68%), spiking recovery rate (accuracy: 87.17% to 112.71%), matrix effect (accuracy: 88.03% to 114.87%), and reproducibility and repeatability of sample preparation (RSD: 1.95% to 7.26%). The performance of proteotypic peptides ApoA-I, ApoE and ApoJ was sufficient for triplex quantitation within a linear range from 16.26 to 1626.41 pmol mL −1, 1.03 to 103.35 pmol mL −1 and 0.86 to 86.46 pmol mL −1 respectively. For all quantified peptides, the determination coefficient ( R 2 ) was >0.997. Besides, the validated LC-MS/MS method has been successfully applied to the quantification of plasma samples in diabetes mellitus and cardiovascular diseases. We anticipate that this assay may provide an alternative method for future clinical applications.